Modeling earthquake-induced wavefields and stresses in alpine mountains with extreme topography - Fabian Limberger; Georg Rümpker; Jan Philipp Kruse; Thibault Duretz (Scientific Reports)
Abstract Earthquakes can trigger slope instabilities such as rockfalls, landslides, and avalanches, posing a significant hazard for residents and infrastructures, particularly in mountainous regions. This risk is further exacerbated by global warming and permafrost degradation, which destabilize surfaces. Hence, our study investigates earthquake-induced wave dynamics at mountain summits, particularly at the Matterhorn (Switzerland) and Tre Cime di Lavaredo (Italy). The selected sites represent exceptional cases of isolated peaks. While these landforms are rare even within alpine environments, they offer crucial boundary cases to explore the upper limits of topographic amplification under seismic excitation. Full wavefield modeling is utilized to simulate the induced resonant oscillations and amplification of seismic signals at the summits compared to adjacent valleys. The simulated amplification (up to 10 times) in the summit depends on the characteristics of motion direction, topography, and presence of permafrost. Major resonance modes are identified at Matterhorn at frequencies of 0.4 Hz and 1.4 Hz. Higher resonance frequencies above 2 Hz are obtained at the smaller rock formation Tre Cime di Lavaredo, indicating mountain-specific resonances. We demonstrate that the presence of a permafrost body inside the mountain tends to reduce seismic amplification by up to 30%. However, this effect is dependent on the amount of permafrost and the wavelength of the seismic waves. Locations of potential slope instabilities on the mountain’s surface are identified based on the dynamic stress changes during the simulated earthquake. We find that locations of stress amplification are mainly at the mountain flanks and are influenced by azimuthal characteristics of the incoming wave. The approach and findings presented in our study have the potential to improve hazard assessments for earthquake-induced slope instabilities, focusing on mountains with extreme geometries.